Customary Law Existency in The Modernization of Criminal Law in Indonesia - Tolkah Tolkah (Fakultas Hukum Universitas Muhammadiyah Magelang, 2021)
Customary law is defined as assets owned by the Indonesian nation and developing in society. However, the existence of customary laws is often questioned to what extent these laws can be applied. In several criminal law cases in Indonesia, several regions still use the customary law system as an alternative to decisions because its role in law enforcement is quite dominant. This study aims to identify the existence of customary law as a modernization of criminal law in Indonesia. This study used a descriptive analytic method with a normative and empirical juridical approach. The data used are secondary data and primary data. The results show that the customary law can be used as a basis of law for developing new criminal laws that are acceptable to the society. Indonesian customary criminal law, which is divided into numerous customary law units, represents the Indonesian nation's original culture, which was once governed by Islamic law. Customary law is very relevant as a consideration for Indonesian criminal law reform, especially in the formulation of the Criminal Code (KUHP).